2017
DOI: 10.1097/md.0000000000007224
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of somatic mutations of cancer-related genes according to microsatellite instability status in Korean gastric cancer

Abstract: In studies of the molecular basis of gastric cancer (GC), microsatellite instability (MSI) is one of the key factors. Somatic mutations found in GC are expected to contribute to MSI-high (H) tumorigenesis. We estimated somatic mutation distribution according to MSI status in 52 matched pair GC samples using the Ion Torrent Ion S5 XL with the AmpliSeq Cancer Hotspot panel.Seventy-five (9.8%) somatic variants consisting of 34 hotspot mutations and 41 other likely pathogenic variants were identified in 34 GC samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…We also did not observe any prognostic significance of signature 1, which includes KDM6B , in either breast or renal clear cell cancer, which indirectly substantiates findings from two other reports on KDM6B not being a marker of good prognosis [40, 41]. Several other gene signatures have been reported for gastrointestinal cancers [4246]. Interestingly, there is no overlap between our signature genes and those identified in these studies.…”
Section: Discussionsupporting
confidence: 90%
“…We also did not observe any prognostic significance of signature 1, which includes KDM6B , in either breast or renal clear cell cancer, which indirectly substantiates findings from two other reports on KDM6B not being a marker of good prognosis [40, 41]. Several other gene signatures have been reported for gastrointestinal cancers [4246]. Interestingly, there is no overlap between our signature genes and those identified in these studies.…”
Section: Discussionsupporting
confidence: 90%
“…MSI is characterized by elevated mutation rates, including mutations of genes encoding targetable oncogenic signaling proteins [ 60 ]. MSI GCs have been shown to harbor more mutations in genes that act as tumor suppressors or oncogenes [ 61 ]. TCGA HotNet analysis of genes mutated within MSI tumors revealed common alterations in major histocompatibility complex class I genes, including beta - 2 microglobulin ( B2M ) and HLA - B [ 4 ].…”
Section: Tcga Gastric Cancer Subtypesmentioning
confidence: 99%
“…With regard to somatic mutations, it has been reported that TP53, KRAS, ARID1A, PIK3CA, ERBB3, PTEN and HLA-B are the commonly mutated genes in gastric cancer (4). In a previous study, TP53 mutations were reported to be the most common in gastric cancer samples, followed by mutations of EGFR, HNF1A, PIK3CA and ERBB2 (7). As of date, several drugs, with molecular targets, have been evaluated for their efficacy in treating cancers, which has been found to be associated with the genetic profile of patients.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, it is important to perform a comprehensive analysis of the relationships of gene alteration status and patient's characteristics. Park et al performed an NGS analysis using a targeted gene panel to detect common as well as rare mutations, and showed that the accumulation of microsatellite instability status contributes to the genetic diversity and complexities in gastric cancer (7).…”
Section: Introductionmentioning
confidence: 99%